Blue sensitive sub-band gap negative photoconductance in SnO2/TiO2 NP bilayer oxide transistor - Pandey U.; Pal N.; Ghosh A.; Suman S.; Biring S.; Pal B.N. (My University, 2025)
Large negative photoconductance (NPC) of SnO2/TiO2 nanoparticles (NPs) heterostructure has been observed with thin film transistor (TFT) geometry and has been investigated using sub-bandgap light (blue) illumination. This negative photoconduction has been detected both in accumulation and depletion mode operation, which effectively reduces the carrier mobility (μ) of the TFT. Moreover, the threshold voltage (Vth) widely shifted in the positive direction under illumination. The combined effects of the reduction of mobility and Vth shifting led to a faster reduction of On (or Off) state current under illumination. The negative photosensitivity of this system is as high as 3.2 A W−1, which has been rarely reported in the earlier literature. Moreover, the variation of On (or Off) current, μ and Vth shift is linear with low-intensity blue light. This SnO2/TiO2 NP bilayer channel has been deposited on top of an ionic dielectric (Li-Al2O3) that reduces its operating voltage of this TFT within 2 V. Furthermore, the device has achieved a saturation mobility of 0.4 cm2 V−1 s−1 with an on/off ratio of 7.4 × 103 in the dark. An energy band diagram model has been proposed based on the type-II heterostructure formation between SnO2/TiO2 semiconductors to explain this NPC mechanism. According to the energy band diagram model, adsorbed H2O molecules of TiO2 NPs created a depleted layer in the heterostructure that accelerated the recombination process of photo-generated carriers rather than its transport. © 2024 The Royal Society of Chemistry